Soil Preparation Studies: II. The Effect of Depth and Method of Soil Preparation and of Organic Material on the Performance of Vitis vinifera (var. Colombar) on Clovelly/Hutton Soil - Saayman, D. (South African Journal of Enology and Viticulture, 2017)
As a follow-up for similar investigations carried out in the irrigation area of the Breede River valley, the effect of different methods of soil preparation on the performance of Colombar/143B on a Hutton/Clovelly soil was studied at Stellenbosch in the Cape coastal area. Results were generally in accordance with those obtained in the Breede River valley studies, and showed no convincing effect of organic material additions but a strong positive effect of depth and efficiency of soil loosening. Root growth was related to the soil volume loosened and to vine performance. Roots tended to concentrate in the surface soil layers in shallow soil but showed a more desirable uniform distribution in delve ploughed soil. Although costly, delve ploughing the soils investigated in this study is clearly economically justifiable, primarily because the vineyard reached its potential production level sooner. The effect of eliminating excess acidity during soil preparation was not studied in this project, and no optimum soil volume could be determined because of the inability of the implements used to attain sufficient depths. These two aspects are regarded as very important and merit further study.